EXPERIMENTAL STUDIES ON SULFANILAMIDES I ABSORPTION - ZOZAYA, JOSE (Universidad Nacional Autónoma de Mexico, CD MEXICO, DF, MEX, 1941)
The absorption rate of sulfanilamide, sulfapyridine, sulfathiazole, sulfaguanidine and sulfadiazine was studied in white mice of about 25 gm weight, fasting for 24 hours The conc of sulfa drugs was measured in blood at different intervals, and in the d
CIENC MEX
Keywords: EXPERIMENTAL, STUDIES, SULFANILAMIDES, ABSORPTION; CIENCIAS MEDICAS; FARMACOLOGIA